Conductive nonwoven fabric-based curved frequency selective surface and method for manufacturing the same
Patent Information
- Application Number
- CN202611066242.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-16
AI Technical Summary
克服了现有技术FSS导电结构和复合材料共固化性能差、曲面成型时难以保持结构精度等问题
(1)本发明提供的基于导电无纺布的曲面频率选择表面实现了与透波复合材料的良好共固化性能和高精度导电结构:采用超薄柔性导电无纺布作为载体,铺贴时完美贴合复杂双曲率模具表面,共固化后形成一体化结构,无褶皱、无架桥,解决了传统刚性FSS无法曲面成型的难题;同时在此基础上,通过曲面激光刻蚀,得到了高精度的FSS导电结构;
Smart Images

Figure CN122931322A_ABST
Abstract
Description
Technical Field
[0001] This invention specifically relates to a curved frequency selective surface based on conductive nonwoven fabric and its preparation method, belonging to the fields of electromagnetic functional composite materials and stealth technology. Background Technology
[0002] A frequency selective surface (FSS) is an artificial electromagnetic structure composed of periodically arranged metal patches or aperture arrays that can selectively transmit or reflect electromagnetic waves in a specific frequency band. Based on this characteristic, FSSs have been widely used in radome bandpass / bandstop filtering, stealth technology, and antenna sub-reflectors.
[0003] As aircraft aerodynamic shapes evolve towards complex curved surfaces, the demand for conformal fairings (FSS) is becoming increasingly urgent. Currently, existing FSS fabrication processes mainly fall into two categories: one involves bonding or pre-placement using metal patches, such as the technical solutions disclosed in Chinese patent applications CN121840203A and CN121688416A; the other involves screen printing using conductive paste, such as patent application CN121394902A, which discloses a pattern structure screen-printed with sheet-like silver / graphite conductive paste. However, the above methods have the following technical drawbacks: (1) Insufficient interfacial bonding stability: The interface properties between the highly conductive metal patch or coating and the composite material are significantly different, resulting in weak interfacial bonding. During service, the patch or coating is easy to separate from the composite matrix, which seriously affects the structural integrity and long-term stability of the electromagnetic performance of the FSS.
[0004] (2) Co-curing molding processability and pattern accuracy are difficult to achieve simultaneously. Specifically, this is reflected in three aspects: a) Patch is difficult to co-cur with composite materials. Patch lacking permeable pores hinders resin flow and is prone to defects in the bonding area; b) Patch or printed coating is prone to displacement during co-curing, making it difficult to guarantee accuracy; c) It is difficult to achieve high-precision patterns on complex hypercurvature surfaces.
[0005] (3) Weight gain caused by patch bonding: Metal patches usually need to be bonded to the substrate by adhesives. The adhesive layer and the patch itself introduce additional non-structural mass, which is particularly unfavorable for aerospace applications with stringent weight requirements.
[0006] Therefore, developing a lightweight FSS material and its preparation method that can achieve good co-curing with wave-transparent composite materials, has good interfacial bonding and high conductivity, can be applied to complex curved surfaces, and has high uniform conductivity and high-precision patterns has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] This invention addresses the shortcomings of existing technologies by providing a curved frequency selective surface (FSS) based on conductive nonwoven fabric and its preparation method. Through the design and fabrication of a conductive nonwoven fabric suitable for FSS structures, the preparation of a co-cured structure of the conductive nonwoven fabric and a microwave-transparent composite material, and laser etching of the conductive structure, an FSS conductive structure is obtained. This structure exhibits high conductivity, a conformal curved surface structure, high pattern fineness, and conductive uniformity. The FSS conductive structure demonstrates excellent surface adhesion to the microwave-transparent composite material, meeting the requirements of complex curved surface structures for fine patterns, high uniformity, and good adhesion. This overcomes the problems of poor co-curing performance of FSS conductive structures and composite materials, and the difficulty in maintaining structural accuracy during curved surface molding, inherent in existing technologies.
[0008] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing a curved frequency selective surface based on conductive nonwoven fabric, the preparation method comprising the following steps: S1. Co-curing molding: The conductive nonwoven fabric is laid on the surface of the uncured wave-transparent composite material to obtain a preform. The preform is cured by heating and pressurizing to obtain an integrated co-cured molded body of conductive nonwoven fabric and wave-transparent composite material. S2. Laser etching: Using laser engraving equipment, a preset periodic frequency selected surface pattern is etched on the conductive non-woven fabric on the surface of the co-cured molded body. The conductive nonwoven fabric consists of a nonwoven fabric and a metal layer covering the surface of the nonwoven fabric, forming a continuous conductive structure.
[0009] Furthermore, the nonwoven fabric has a thickness of 10~100μm and a fiber diameter of 3~20μm; the metal layer has a thickness of 1~15μm; the surface sheet resistance of the conductive nonwoven fabric is ≤0.1Ω / sq.; the areal density of the nonwoven fabric is 5~50g / m², and the porosity is 60~85%.
[0010] Furthermore, the ratio of the thickness of the nonwoven fabric to the diameter of the nonwoven fabric fibers is 3 to 10.
[0011] Furthermore, the method for preparing the conductive nonwoven fabric includes the following steps: (1) Conductivity treatment: A metal conductive seed layer is deposited on the surface of the nonwoven fabric using a vacuum evaporation process; (2) Electroplating thickening: Using the non-woven fabric treated in step (1) as the cathode, a nickel-coated copper metal layer is plated on the surface of the conductive seed layer by electroplating process to obtain conductive non-woven fabric.
[0012] Furthermore, in step (1), the thickness of the conductive seed layer is 0.05~0.5μm.
[0013] Furthermore, in step (2), the thickness of the nickel-coated copper metal layer is 1~15μm.
[0014] Furthermore, in step (1), the conductive seed layer is a copper layer, a silver layer, or a nickel layer.
[0015] Furthermore, in step (2), the plating solution used in the electroplating process contains copper salt and nickel salt, and in the obtained nickel-coated copper metal layer, the mass percentage of nickel is 5~30% and the mass percentage of copper is 70~95%.
[0016] Further, in step S1, the wave-transparent composite material is a glass fiber reinforced resin matrix composite material or a quartz fiber reinforced resin matrix composite material; the resin is epoxy resin or bismaleimide resin.
[0017] Furthermore, in step S2, the laser engraving equipment is an ultraviolet laser engraving machine or a fiber laser engraving machine, and the line width accuracy of laser etching is controlled within ±0.05mm.
[0018] Furthermore, in step S2, the preset periodic frequency selection surface pattern is at least one of a dipole array, a Jerusalem cross array, a square ring array, or a complementary open resonant ring array.
[0019] Furthermore, in step S1, the co-curing molding process is autoclave molding, compression molding, or vacuum bag molding; Furthermore, in step S1, the curing temperature range is 80~200℃, and the pressure range is 0.1~1.0MPa.
[0020] Furthermore, in step S2, the depth of laser etching is controlled to be 1.5 to 5.0 times the thickness of the conductive nonwoven fabric, and not less than 50 μm.
[0021] The present invention also provides a curved frequency selective surface based on conductive nonwoven fabric, which is obtained by the preparation method provided by the present invention.
[0022] The complex curved frequency selective surface made of conductive nonwoven fabric provided by this invention can be applied to aircraft radomes, stealth skins, or electromagnetic windows.
[0023] The beneficial effects of this invention are: (1) The curved frequency selective surface based on conductive nonwoven fabric provided by the present invention achieves good co-curing performance and high-precision conductive structure with wave-transparent composite material: using ultra-thin flexible conductive nonwoven fabric as carrier, it perfectly fits the complex double curvature mold surface during laying, and forms an integrated structure after co-curing, without wrinkles or bridging, solving the problem that traditional rigid FSS cannot be curved; at the same time, on this basis, a high-precision FSS conductive structure is obtained by curved laser etching. (2) The present invention forms a dense nickel-coated copper metal layer on the surface of nonwoven fabric through a composite coating process of "evaporation + electroplating", with a sheet resistance as low as 0.1Ω / sq. At the same time, through the structural design of nonwoven fabric (fiber diameter, nonwoven fabric thickness, thickness to fiber diameter ratio, metal layer thickness), the resistance distribution of the formed FSS structure is highly uniform and consistent, which meets the requirements of FSS for high conductivity and high resistance consistency of conductive layer. (3) The present invention adopts a combination of nickel-coated copper metal layer structure and fiber composite structure, which forms a mechanical interlocking structure after curing, thereby improving the interface bonding performance. Attached Figure Description
[0024] Figure 1 This is a process flow diagram of the present invention; Figure 2 This is a photograph of the periodic FSS pattern after laser etching in Example 4; Figure 3 This is a SEM image of the conductive treatment of the ultrathin nonwoven fabric in Example 4. Detailed Implementation
[0025] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.
[0027] The core concept of this invention is as follows: using an ultra-thin nonwoven fabric as a carrier, a composite coating process of "evaporation + electroplating" is used to make it conductive, resulting in a conductive nonwoven fabric with both high conductivity and high breathability, suitable for preparing complex curved surface frequency selective surface structures; then, this conductive fabric is used as the conductive structural layer of the FSS (Frequency Selective Surface) and co-cured with a preform of a wave-transparent composite prepreg; finally, high-precision periodic patterns are processed on the surface of the conductive fabric by direct laser etching. By designing the structure of the nonwoven fabric to have good deformability, co-curing performance, interfacial bonding strength, and high conductivity uniformity, it is possible to combine laser etching to obtain an FSS conductive structure with high pattern precision and high conductivity consistency on complex curved surfaces.
[0028] The process route of this invention is compatible with traditional composite material molding processes, requires no special equipment, and is easy to implement for mass production in engineering. The complex curved surface frequency selective surface preparation method provided by this invention has both excellent curved surface conformal capability and interfacial bonding, and has important application value in the following scenarios: (a) aircraft radome: achieving in-band wave transmission and out-of-band stealth; (b) stealth skin: combined with wave-absorbing structures to achieve multi-spectral compatible stealth; (c) electromagnetic windows: electromagnetic transmission components such as radomes and fairings; (d) 5G communication housing: achieving selective transmission in specific frequency bands.
[0029] The main purpose of this application is to solve the problem that it is difficult to prepare FSS conductive structures with good interface and high precision co-curing using existing technologies such as metal patch and screen printing. In order to solve this problem, based on the innovative use of conductive nonwoven fabric as conductive substrate, the following technical problems need to be solved at the same time: (1) to achieve good conductivity of conductive nonwoven fabric, good layability on complex curved surfaces, and good co-curing and good interface bonding with wave-transparent structural components; (2) to achieve the precision and conductivity accuracy of FSS conductive structure.
[0030] This invention solves the above problems by combining the design and fabrication of an ultrathin conductive nonwoven fabric structure, co-curing it with a wave-transparent composite material, and laser etching, thus achieving the fabrication of a high-precision integrated FSS conductive structure. The process flow diagram of this invention is shown below. Figure 1 As shown.
[0031] The present invention provides a method for preparing a curved frequency selective surface, comprising the following steps: S1. Co-curing molding: The conductive nonwoven fabric provided by the present invention is laid on the surface of the uncured wave-transparent composite material to obtain a preform. The preform is cured by heating and pressurizing to obtain an integrated co-cured molded body of conductive nonwoven fabric and wave-transparent composite material. S2. Laser Etching: Using laser engraving equipment, a preset periodic frequency selected surface pattern is etched on the conductive nonwoven fabric on the surface of the co-cured molded body.
[0032] It should be noted that the wave-transparent composite material provided by the present invention is a preform of wave-transparent composite material prepreg, which is laid out according to the design of the wave-transparent composite material prepreg; during the preparation of the curved frequency selection surface, non-woven fabric is laid on the surface of the preform.
[0033] Specifically, in step S1, the wave-transparent composite material is a glass fiber reinforced resin matrix composite material or a quartz fiber reinforced resin matrix composite material; the resin is epoxy resin or bismaleimide resin.
[0034] Specifically, in step S2, the laser engraving equipment is an ultraviolet laser engraving machine or a fiber laser engraving machine, and the line width accuracy of laser etching is controlled within ±0.05mm.
[0035] Specifically, in step S2, the preset periodic frequency selection surface pattern is at least one of a dipole array, a Jerusalem cross array, a square ring array, or a complementary open resonant ring array.
[0036] Specifically, in step S1, the co-curing molding process is autoclave molding, compression molding, or vacuum bag molding; the curing temperature range is 80~200℃, and the pressure range is 0.1~1.0MPa.
[0037] Specifically, in step S2, the depth of laser etching is controlled to be 1.5 to 5.0 times the thickness of the conductive nonwoven fabric, and not less than 50 μm.
[0038] It should be noted that the vacuum evaporation process, electroplating process, and laser etching process provided by this invention involve commonly used equipment, as long as they can achieve the purpose of this invention.
[0039] In some embodiments, the electroplating process uses a current density of 0.5 A / dm² to 2.0 A / dm² and an electroplating time of 5 to 30 min. Preferably, the current density is 0.5 A / dm², 1.2 A / dm², or 1.5 A / dm², and the electroplating time is 10 min, 15 min, or 26 min.
[0040] In some embodiments, the laser etching uses an ultraviolet laser engraving machine with a power of 5-20W, a frequency of 30-60kHz, and a scanning speed of 400-600mm / s; preferably, the power is 8-10W, the frequency is 50kHz, and the scanning speed is 500mm / s.
[0041] Unlike existing technologies that use metal patches or coatings, this invention uses ultra-thin conductive nonwoven fabric. The nonwoven fabric has a loose, porous structure, giving it deformability and excellent layability, allowing it to form a good fit with complex curved wave-transparent structures. Furthermore, the porous structure of the nonwoven fabric allows for effective adhesive penetration and extrusion to remove bubbles during co-curing, resulting in a well-formed co-cured structure. This avoids problems such as wrinkles and bridging caused by poor deformability of metal patches during installation, and also avoids the problem of air entrapment and delamination between patches or coatings and the wave-transparent prepreg due to their lack of air permeability.
[0042] To simultaneously meet the requirements for high permeability, interfacial bonding, electrical resistance consistency, and fine conductive structure of nonwoven fabrics when applied to FSS structures, the structural morphology of the ultra-thin nonwoven fabrics and their conductive nonwoven fabrics was strictly controlled. This invention provides a conductive nonwoven fabric, which consists of a nonwoven fabric and a metal layer covering the surface of the nonwoven fabric, forming a continuous conductive structure; the thickness of the nonwoven fabric is 10~100μm, and the fiber diameter is 3~20μm; the thickness of the metal layer is 1~15μm; the surface sheet resistance of the conductive nonwoven fabric is ≤0.1Ω / sq.; the areal density of the nonwoven fabric is 5~50g / m², and the porosity is 60~85%.
[0043] Specifically, the ratio of the thickness of the nonwoven fabric to the diameter of the nonwoven fabric fibers is 3 to 10.
[0044] It's understandable that the thickness of the nonwoven fabric should be less than 100μm to avoid abrupt changes in local resistance. When the nonwoven fabric thickness exceeds 100μm, its deformability decreases, making it prone to wrinkles during installation. This not only results in insufficient installation processability but also creates low-resistance regions in the final FSS structure, leading to strong reflections and other adverse effects. Controlling the fiber diameter to ≥5μm is to maintain the adhesive permeability of the metal-plated nonwoven fabric while ensuring good interfacial bonding. After metal plating, to meet the resistance requirements of the FSS structure (below 0.1Ω / sq.), the plating thickness must be at least 1 micrometer but not exceed 15 micrometers. A larger plating thickness and fiber diameter ratio significantly reduces the porosity between the nonwoven fabric fibers, affecting permeability. Furthermore, a higher metal interface ratio leads to poor interfacial bonding between the final conductive and wave-transparent structures, causing a rapid decline in peel performance. Controlling the fiber diameter to ≤20μm maintains the precision and consistency of the conductive structure. When the fiber diameter is too high, larger gaps are created between the overlapping fibers. Simultaneously, when the thickness is less than 100 μm, the thickness-to-fiber diameter ratio is small, leading to issues such as fiber breakage, edge defects, and large areas of fiber absence in the conductive connection areas of the etched structure. This results in poor consistency in the conductive connection areas, failing to meet the conductivity uniformity requirements of the FSS structure. Controlling the thickness-to-fiber diameter ratio to 3-10 aims to achieve high conductivity consistency across all areas of the final conductive structure, forming a fine conductive structure while avoiding interface and wrinkle problems. When the thickness-to-fiber diameter ratio is ≤3, the uniformity of the metallized fiber coverage deteriorates, leading to the appearance of insulating areas ≥0.02 mm at the edges of the residual conductive connection structure after etching, and poor internal conductivity consistency. This is unacceptable for structures with small conductive connection linewidths, especially for nonwoven fabrics with larger fiber diameters, where edge defects are more likely to occur. When the thickness-to-fiber diameter ratio is ≥10, the adhesive penetration of the nonwoven fabric after metallization deteriorates, affecting interfacial bonding. Controlling the surface sheet resistance of the ultrathin conductive cloth to ≤0.1Ω / sq. is to meet the high conductivity requirement of the FSS structure for the conduction of fine connections.
[0045] In some embodiments, the ultrathin nonwoven fabric is at least one of polyester fiber nonwoven fabric, aramid fiber nonwoven fabric, meltblown polyester fiber nonwoven fabric, and meltblown polyphenylene sulfide fiber nonwoven fabric.
[0046] The present invention relates to a method for preparing conductive nonwoven fabric, comprising the following steps: (1) Conductivity treatment: A metal conductive seed layer is deposited on the surface of the nonwoven fabric using a vacuum evaporation process; (2) Electroplating thickening: Using the non-woven fabric treated in step (1) as the cathode, a nickel-coated copper metal layer is plated on the surface of the conductive seed layer by electroplating process to obtain conductive non-woven fabric.
[0047] In some embodiments, in step (1), the thickness of the conductive seed layer is 0.05~0.5μm. Controlling the seed layer thickness to 0.05~0.5μm is to ensure that the metal layer obtained in the next step of plating can well cover the fiber and has fewer defects.
[0048] In some embodiments, in step (1), the conductive seed layer is a copper layer, a silver layer, or a nickel layer.
[0049] In some embodiments, in step (2), the thickness of the nickel-coated copper metal layer is 1~15μm.
[0050] In some embodiments, in step (2), the plating solution used in the electroplating process contains copper salt and nickel salt, and in the obtained nickel-coated copper metal layer, the mass percentage of nickel is 5~30% and the mass percentage of copper is 70~95%. Controlling the plating metal layer to be copper + nickel improves the interfacial bonding force of co-curing compared with using copper plating alone, and increases corrosion resistance. Compared with using nickel plating alone, it improves conductivity. The preferred ratio of the two is...
[0051] By controlling the above parameters, the areal density of the nonwoven fabric obtained in this application is typically 5~50 g / m², and the porosity is 60~85%; the areal density of the conductive nonwoven fabric is 15~70 g / m², and the porosity is 50~80%. The corresponding ultrathin conductive nonwoven fabrics prepared have good layability and resin permeability, good bonding with the resin interface, and good uniformity of resistance distribution in the conductive connection structure formed after etching. Large-area insulating regions affecting the continuity of conductivity are not formed on the sides or inside. Therefore, the resistance dispersion coefficient of the conductive structure lines is generally less than 10%, which is satisfactory. To meet the requirements of FSS structure, typically for nonwoven fabrics with fiber diameter ≥15μm and ≤20μm, even if the thickness-to-fiber diameter ratio is 3~4, the gap of insulating resin between metal-plated fibers is usually less than 0.08mm. For nonwoven fabrics with fiber diameter 3~8μm and a thickness-to-fiber diameter ratio of 3.5~10, the gap of insulating resin between metal-plated fibers is generally less than 0.02mm, achieving a very high conductivity uniformity and meeting the requirement of higher conductivity uniformity for FSS structures with narrower line widths.
[0052] Preferably, the fiber diameter is controlled to be 5-10 micrometers and the ratio of thickness to fiber diameter is 3-6; or the fiber diameter is controlled to be 10-20 micrometers and the ratio of thickness to fiber diameter is 4-6, which has the best interfacial bonding performance, good layability, and uniform conductivity.
[0053] The present invention also provides a curved frequency selective surface based on conductive nonwoven fabric, which is obtained by the preparation method provided by the present invention.
[0054] The complex curved frequency selective surface made of conductive nonwoven fabric provided by this invention can be applied to aircraft radomes, stealth skins, or electromagnetic windows.
[0055] The above-mentioned technical features are inseparable and support each other in their function, achieving effects that cannot be achieved by a single technical feature, and solving the following technical problems: (1) achieving good conductivity of conductive nonwoven fabric, good layability on complex curved surfaces, and good co-curing and good interface bonding with wave-transparent structural components; (2) achieving precision and conductivity accuracy of FSS conductive structure.
[0056] Regarding technical issue (1): Controlling the thickness of the nonwoven fabric to 10~100μm gives it good deformability, meeting the requirements for laying; through vapor deposition and electroplating processes, nickel-coated copper and nickel-coated silver layers are plated on the surface of the nonwoven fabric, giving it good conductivity, allowing the surface sheet resistance to be ≤0.1Ω / sq. even with a small coating thickness, meeting the requirements of the FSS structure; the above-mentioned high conductivity treatment process also allows the coating thickness of the low resistance nonwoven fabric to be controlled to 1~15μm, combined with controlling the fiber diameter to 5~20μm, the areal density of the nonwoven fabric to 5~50g / m², and the porosity to 60~85%, so that the nonwoven fabric, after being highly conductive, still maintains good permeability and porous structure, meeting the requirements for adhesive penetration, possessing good co-curing performance, and also maintaining good laying performance; maintaining good permeability and porous structure, plus the presence of the outer nickel plating layer, gives the conductive nonwoven fabric and the wave-transparent structure good co-curing interface performance. Therefore, it achieves good adhesion to complex surfaces, good co-curing performance, and good co-curing interface.
[0057] Regarding technical issue (2): The precision and conductivity accuracy of the FSS conductive structure are key to its frequency selectivity performance. That is, the FSS structure must possess precise structural dimensions and uniform, controllable conductivity in all areas. This invention employs a co-laying and co-curing process for conductive nonwoven fabric, forming a co-cured integrated structure with the wave-transparent structure. Laser etching is then used to obtain a precisely dimensional conductive structure. In contrast, traditional methods first create the conductive structure and then co-cur it with the composite material, making structural deformation almost inevitable. By controlling the co-curing temperature and pressure, structural deformation and thickness-to-wrinkle penetration of the nonwoven fabric-wave-transparent composite material are avoided after co-curing. Simultaneously, by controlling the etching precision (linewidth accuracy controlled within ±0.05mm) and etching depth (depth controlled to 1.5~5.0 times the thickness of the conductive nonwoven fabric, and not less than 50μm), unnecessary conductive nonwoven fabric areas are completely etched, while excessive etching damage to the wave-transparent structure is avoided. Furthermore, the porous structure of the conductive nonwoven fabric inevitably affects the conductivity continuity and uniformity of the fine conductive structure, reducing conductivity accuracy. By controlling the ratio of nonwoven fabric thickness to nonwoven fabric fiber diameter to 3-10, the etched fine conductive structure achieves the required conductivity accuracy while ensuring that the nonwoven fabric thickness does not affect layability, and excessive etching damage to the wave-transparent structure is avoided. The comprehensive control of these technical parameters achieves precision and conductivity accuracy in the FSS conductive structure.
[0058] To better illustrate the embodiments of the present invention, the present invention will be further described in detail below through specific examples.
[0059] Example 1 This embodiment provides a method for fabricating a bandpass-type FSS for X-band radomes.
[0060] (1) Material preparation: The ultra-thin nonwoven fabric is made of polyester fiber nonwoven fabric with a fiber diameter of 12μm, a nonwoven fabric thickness of 51μm, a thickness-to-fiber diameter ratio of 4.25, a surface density of 17g / m², and a porosity of 70%.
[0061] Wave-transparent composite material: Quartz fiber reinforced cyanate ester resin prepreg is selected, with a single layer thickness of 0.125mm and a layup design of [0 / 90]4s.
[0062] (2) Preparation of ultrathin conductive nonwoven fabric, including the following steps: 1) Conductivity treatment: The ultra-thin nonwoven fabric is loaded into a vacuum evaporation equipment, the base vacuum is evaporated to 5×10⁻³Pa, and metallic copper is deposited by evaporation. The deposition thickness is controlled to 0.2μm to obtain a nonwoven fabric with a conductive seed layer on the surface.
[0063] 2) Electroplating thickening: Electroplating solution preparation: 80 g / L copper sulfate, 20 g / L nickel sulfate, 30 g / L sulfuric acid, and appropriate amount of brightener. Using the non-woven fabric treated in step S1 as the cathode and the phosphor bronze plate as the anode, with a current density of 1.5 A / dm² and an electroplating time of 15 min, a nickel-coated copper metal layer with a total thickness of approximately 8 μm was obtained, containing 82% copper and 18% nickel by mass. The sheet resistance of the conductive fabric was tested to be 0.006 Ω / sq.
[0064] (3) Preparing a frequency-selective surface, including the following steps: S1, Co-curing molding Quartz / cyanate prepreg was laid up according to the design, and the outermost layer was an ultrathin conductive cloth (conductive side facing out). The mixture was placed in an autoclave and cured at 180°C for 2 hours under a pressure of 0.6 MPa. After curing, an integrated FSS / composite laminate was obtained, and its tensile strength was tested using the coating pull-out method (GB / T 5210), showing a strength of 24.1 MPa.
[0065] S2, Laser Etching A UV laser engraving machine was used, with a power of 8W, a frequency of 50kHz, and a scanning speed of 500mm / s, to etch a periodic square ring pattern onto the surface of conductive cloth, controlling the etching depth to 100μm. The outer side length of the square ring was 8mm, the inner side length was 6mm, and the period was 10mm. The etching linewidth was controlled within 0.05mm.
[0066] The results showed that the prepared ultrathin conductive nonwoven fabric was easy to lay on the surface of the prepreg, and exhibited good resin permeability and interfacial bonding (tensile strength 24.1 MPa). Electromagnetic performance tests on the prepared FSS structure showed that, within the 8.2 GHz-12.4 GHz frequency band, the insertion loss was ≤0.5 dB and the out-of-band rejection was ≥15 dB, meeting the design specifications. After high and low temperature cycling and damp heat treatment, the FSS pattern showed no peeling or cracking.
[0067] Example 2
[0068] This embodiment provides a method for fabricating an integrated radar absorber / transmitter stylist (FSS) for stealth skin.
[0069] (1) Material preparation The ultra-thin nonwoven fabric is made of aramid fiber, with a fiber diameter of 16μm, a nonwoven fabric thickness of 82μm, a thickness-to-fiber diameter ratio of 5.1, a surface density of 25 g / m², and a porosity of 76%.
[0070] Wave-transparent composite material: Glass fiber reinforced, medium-temperature curing epoxy resin prepreg is used, with a single layer thickness of 0.125 mm and a layup design of [0 / 90]. 2s .
[0071] (2) Preparation of ultrathin conductive nonwoven fabric, including the following steps: 1) Conductivity treatment: The ultra-thin nonwoven fabric is loaded into a vacuum evaporation equipment, the base vacuum is evaporated to 5×10⁻³Pa, metallic silver is deposited by evaporation, and the deposition thickness is controlled to 0.1μm to obtain a nonwoven fabric with a conductive seed layer on the surface.
[0072] 2) Electroplating thickening: The electroplating solution was prepared in the same manner as in Example 1. The nonwoven fabric treated in step S1 was used as the cathode and the phosphor bronze plate as the anode. The current density was 1.5 A / dm² and the electroplating time was 26 min. The total thickness of the nickel-coated copper metal layer was approximately 12 μm, with a copper mass content of 85% and a nickel mass content of 15%. The sheet resistance of the conductive fabric was tested to be 0.004 Ω / sq.
[0073] (3) Preparing a frequency-selective surface, including the following steps: S1, Co-curing molding Glass fiber / medium-temperature curing epoxy resin prepreg was laid out according to the design, and an ultra-thin conductive cloth (conductive side facing out) was laid as the outermost layer. The mixture was placed in an autoclave, heated to 120°C, and held at that temperature for 2 hours under a pressure of 0.4 MPa. After curing, an integrated FSS / composite laminate was obtained, and its tensile strength was tested using the coating pull-out method (GB / T 5210), showing a strength of 28.5 MPa.
[0074] S2, Laser Etching A Jerusalem cross pattern was etched onto the surface of conductive cloth using an ultraviolet laser engraving machine with a power of 10W, a frequency of 50kHz, and a scanning speed of 500mm / s. The etching depth was controlled to be 150μm. The cross height or length of the structural unit was 5mm, the cross engraving line width was 1mm, the length of the rectangle at the end of the cross was 2mm and the width was 1mm, and the spacing between the crosses was 0.5mm.
[0075] The results showed that the prepared ultrathin conductive nonwoven fabric was easy to lay on the surface of the prepreg, and had good resin penetration and interfacial bonding (tensile strength 28.5 MPa). No wrinkling of the nonwoven fabric was observed during the laying process, and it adhered perfectly to the surface. Electromagnetic performance tests were conducted on the prepared FSS structure, and the results showed that the FSS structure had a wave transmission window in the 5GHz±0.5GHz frequency band, reflected at other frequency bands, and had good mechanical properties and air permeability.
[0076] Example 3
[0077] This embodiment provides a method for fabricating a bandpass-type FSS for use in X-band radomes.
[0078] (1) Material preparation The ultra-thin nonwoven fabric is made of meltblown polyester fiber nonwoven fabric with a fiber diameter of 6 μm, a nonwoven fabric thickness of 29 μm, a thickness-to-fiber diameter ratio of 4.83, a surface density of 29 g / m², and a porosity of 72%.
[0079] Wave-transparent composite material: Quartz fiber reinforced bismaleimide resin 5429 prepreg is used, with a single layer thickness of 0.250 mm and a layup design of [0 / 90]. 2s The paving shape is a single curved surface with a radius of curvature of 350mm.
[0080] (2) Preparation of ultrathin conductive nonwoven fabric, including the following steps: 1) Conductivity treatment: The ultra-thin nonwoven fabric is loaded into a vacuum evaporation equipment, the base vacuum is evaporated to 3×10⁻³Pa, and metallic copper is deposited by evaporation. The deposition thickness is controlled to 0.05μm to obtain a nonwoven fabric with a conductive seed layer on the surface.
[0081] 2) Electroplating thickening Electroplating solution preparation: 92 g / L copper sulfate, 15 g / L nickel sulfate, 30 g / L sulfuric acid, and appropriate amount of brightener. Using the non-woven fabric treated in step S1 as the cathode and the phosphor bronze plate as the anode, with a current density of 0.5 A / dm² and an electroplating time of 10 min, a nickel-coated copper metal layer with a total thickness of approximately 3 μm was obtained, containing 91% copper and 9% nickel by mass. The sheet resistance of the conductive fabric was tested to be 0.015 Ω / sq.
[0082] (3) Preparing a frequency-selective surface, including the following steps: S1, Co-curing molding Quartz fiber reinforced bismaleimide resin 5429 prepreg was laid out according to the design, and the outermost layer was an ultra-thin conductive cloth (conductive side facing out). The mixture was placed in an autoclave, and the temperature was raised to 150℃ and held for 2 hours at a pressure of 0.6 MPa according to the curing process. The temperature was then raised to 195℃ and held for 2 hours at a pressure of 0.6 MPa. After curing, an integrated FSS / composite laminate was obtained, and the tensile strength was tested using the coating pull-out method (GB / T 5210), showing a strength of 28.7 MPa.
[0083] S2, Laser Etching A UV laser engraving machine was used, with a power of 8W, a frequency of 50kHz, and a scanning speed of 500mm / s, to etch a periodic square ring pattern on the surface of conductive cloth, controlling the etching depth to 90μm. The outer side length of the square ring was 8mm, the inner side length was 5mm, the period was 10mm, and the etching linewidth was controlled within 0.02mm.
[0084] The results showed that the prepared ultrathin conductive nonwoven fabric was easy to lay on the surface of the prepreg, with good resin penetration and interfacial bonding (tensile strength 28.7 MPa). No wrinkling was observed in the nonwoven fabric during the laying process, and it adhered perfectly to the surface. Electromagnetic performance tests were conducted on the prepared FSS structure, and the results showed that the insertion loss was ≤0.5 dB and the out-of-band rejection was ≥15 dB in the 7.6 GHz-11.9 GHz frequency band, meeting the design specifications. After high and low temperature cycling and damp heat treatment, the FSS pattern did not peel off or crack. The resistance dispersion coefficient of each part was 4.6%. SEM observation showed that the fiber coverage on the pattern reached 95%, and the gap size of the insulating resin in the conductive fiber covered area was less than 8 μm, exhibiting excellent conductivity uniformity.
[0085] Example 4
[0086] This embodiment provides a method for fabricating a radar-absorbing FSS structure for stealth skin.
[0087] (1) Material preparation The ultra-thin nonwoven fabric is made of meltblown polyphenylene sulfide fiber nonwoven fabric with a fiber diameter of 7.6μm, a nonwoven fabric thickness of 26μm, a thickness-to-fiber diameter ratio of 3.47, a surface density of 26g / m², and a porosity of 82%.
[0088] Wave-transparent composite material: Quartz fiber reinforced bismaleimide resin 5429 prepreg is used, with a single layer thickness of 0.250 mm and a layup design of [0 / 90]. 2s The tiling shape is a hyperboloid structure with a horizontal curvature radius of 800mm and a vertical curvature radius of 600mm.
[0089] (2) Preparation of ultrathin conductive nonwoven fabric, including the following steps: 1) Conductivity treatment: The ultra-thin nonwoven fabric is loaded into a vacuum evaporation equipment, the base vacuum is evaporated to 1×10⁻³Pa, and metallic copper is deposited by evaporation. The deposition thickness is controlled to 0.13μm to obtain a nonwoven fabric with a conductive seed layer on the surface.
[0090] 2) Electroplating thickening: Electroplating solution preparation: 90 g / L copper sulfate, 20 g / L nickel sulfate, 32 g / L sulfuric acid, and appropriate amount of brightener. Using the non-woven fabric treated in step S1 as the cathode and the phosphor bronze plate as the anode, with a current density of 1.2 A / dm² and an electroplating time of 10 min, a nickel-coated copper metal layer with a total thickness of approximately 5 μm was obtained, containing 88% copper and 12% nickel by mass. The sheet resistance of the conductive fabric was tested to be 0.009 Ω / sq.
[0091] (3) Preparing a frequency-selective surface, including the following steps: S1, Co-curing molding Quartz fiber reinforced bismaleimide resin 5429 prepreg was laid out according to the design, with the outermost layer being an ultra-thin conductive cloth (conductive side facing out). The mixture was placed in an autoclave and cured at 150°C for 2 hours under a pressure of 0.6 MPa, then further heated to 195°C and held for 2 hours under a pressure of 0.6 MPa. After curing, an integrated FSS / composite laminate was obtained, and its tensile strength was tested using the coating pull-out method (GB / T 5210), showing a strength of 33.2 MPa.
[0092] S2, Laser Etching A UV laser engraving machine was used, set to 8W power, 50kHz frequency, and 500mm / s scanning speed, to etch a complementary open-loop resonant ring pattern onto the surface of conductive fabric. The rings were circular with an outer diameter of 12mm, an inner diameter of 10mm, and a notch length of 2mm. The etching depth was controlled to 90μm, and the etching linewidth was controlled within 0.03mm. A photograph of the periodic FSS pattern after laser etching is shown below. Figure 2 As shown.
[0093] The results showed that the prepared ultrathin conductive nonwoven fabric was easy to lay on the surface of the prepreg, with good resin penetration and interfacial bonding (tensile strength 33.2 MPa). No wrinkling was observed in the nonwoven fabric during the laying process, and it adhered perfectly to the surface. The electromagnetic properties of the prepared FSS structure met the design specifications, and the FSS pattern was firmly bonded to the substrate. The resistance at the two open ends of each ring was measured, with a coefficient of variation of 6.9%. The SEM image of the conductive ultrathin nonwoven fabric is shown below. Figure 3 As shown, SEM observation revealed that the fiber coverage on the pattern reached 91%, and the gap size of the metal-plated fibers was less than 18 μm, which is less than 0.9% of the width of the conductive ring, indicating excellent conductivity uniformity.
[0094] Comparative Example 1 Using traditional PCB processes: copper foil was deposited on a 0.1 mm thick polyimide film, an FSS pattern was etched, and then a secondary adhesive film was used to bond it to the surface of the quartz fiber reinforced bismaleimide resin 5429 hyperboloid composite material of Example 4. Results showed that wrinkles appeared on the hyperboloid specimen; after thermal cycling, the edges warped, and C-scan analysis indicated a large number of unwetted pores in some copper foil areas and the composite material. A furnace-tested sample was prepared by bonding the copper foil PI film and the composite material, yielding a tensile strength of 2.5 MPa.
[0095] Comparative Example 2 The direct electroplating process was adopted: after spraying conductive paint onto the surface of the quartz fiber reinforced bismaleimide resin 5429 hyperboloid composite material in Example 4, a metal layer was directly electroplated, and then laser etching was used to obtain the ring structure.
[0096] The results showed that the conductive paint had poor adhesion to the substrate, and some areas peeled off; the electroplating layer was uneven, and the coefficient of variation of the resistance at the two open ends of each ring reached 19.2%. By spraying conductive paint onto the composite material plate and electroplating a metal layer to prepare a furnace test sample, a tensile strength of 1.2 MPa was obtained.
[0097] Comparative Example 3 This comparative example uses the same method as Example 1 to prepare an FSS, except that the prepared polyester fiber nonwoven fabric has a thickness of 150 μm and a fiber diameter of 15 μm, which exceeds the thickness range defined in this invention.
[0098] The results showed that wrinkles appeared during the installation process. This was because the non-woven fabric was too thick and its deformability was significantly reduced. When it was installed on a complex curved surface, it caused compression wrinkles, and compression marks were visible on the surface after curing.
[0099] Comparative Example 4 This comparative example uses the same method as Example 1 to prepare an FSS, except that the polyester fiber diameter is 3μm, the nonwoven fabric thickness is 30μm, and the fiber diameter is smaller than the range defined in this invention.
[0100] The results showed poor interfacial bonding. This was because when the fiber diameter was too small, although the fiber interweaving density was high, the porosity between the fibers decreased sharply after metal plating, the resin penetration channels were blocked, and the resin could not effectively wet the fibers during co-curing. The tensile strength tested was only 1.75 MPa.
[0101] Comparative Example 5 This comparative example uses the same method as Example 1 to prepare an FSS, except that in step (2) of step (2), the metal layer is pure copper instead of nickel-coated copper.
[0102] The results showed that the interfacial bonding between the pure copper plating and the wave-transparent composite material was poor, with a tensile strength of only 17.62 MPa. Furthermore, the pure copper plating may also have disadvantages such as insufficient corrosion resistance and deterioration in long-term service performance.
[0103] Comparative Example 6 This comparative example uses the same method as Example 1 to prepare an FSS, except that in step S2 of step (3), the laser etching depth is insufficient, and the etching depth is 30 μm.
[0104] The results showed that when the etching depth was insufficient, the conductive layer was not completely cut off, and there was still a conductive connection between adjacent FSS units.
[0105] The composite materials prepared in the embodiments and comparative examples of the present invention were subjected to performance tests, and the test methods involved are as follows: (1) Interface bonding: Test the tensile strength, refer to the coating tensile test GB / T 5210 standard for testing FSS / composite laminates.
[0106] (2) High and low temperature cycle and damp heat treatment: -20℃ / 1h + 150℃ / 1h cycle 20 times; boiled in water at 70℃ for 7 days.
[0107] (3) Resistance dispersion coefficient: Take the same etched structural unit with a length / line width ≥ 5, slightly polish the two ends of the structure to expose the metal plating, and then coat it with conductive silver paste; after drying, use a micro ohmmeter to contact the conductive silver paste and test the resistance. Select no less than 6 etched structural units in total.
[0108] (4) Conductivity uniformity: evaluated by resistance dispersion coefficient.
[0109] The performance test data of the composite materials prepared in the examples and comparative examples are shown in Table 1.
[0110] Table 1. Test data of some properties of the composite materials prepared in the examples and comparative examples.
[0111] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0112] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A method for preparing a curved frequency-selective surface based on conductive nonwoven fabric, characterized in that, The preparation method includes the following steps: S1. Co-curing molding: The conductive nonwoven fabric is laid on the surface of the uncured wave-transparent composite material to obtain a preform. The preform is cured by heating and pressurizing to obtain an integrated co-cured molded body of conductive nonwoven fabric and wave-transparent composite material. S2. Laser etching: Using laser engraving equipment, a preset periodic frequency selected surface pattern is etched on the conductive non-woven fabric on the surface of the co-cured molded body. The conductive nonwoven fabric consists of a nonwoven fabric and a metal layer covering the surface of the nonwoven fabric, forming a continuous conductive structure.
2. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 1, characterized in that, The nonwoven fabric has a thickness of 10~100μm and a fiber diameter of 3~20μm. The thickness of the metal layer is 1~15μm; The surface sheet resistance of the conductive nonwoven fabric is ≤0.1Ω / sq.; The nonwoven fabric has a surface density of 5~50 g / m² and a porosity of 60~85%.
3. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 2, characterized in that, The ratio of the thickness of the nonwoven fabric to the diameter of the nonwoven fibers is 3 to 10.
4. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 2, characterized in that, The method for preparing the conductive nonwoven fabric includes the following steps: (1) Conductivity treatment: A metal conductive seed layer is deposited on the surface of the nonwoven fabric using a vacuum evaporation process; (2) Electroplating thickening: Using the non-woven fabric treated in step (1) as the cathode, a nickel-coated copper metal layer is plated on the surface of the conductive seed layer by electroplating process to obtain conductive non-woven fabric.
5. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 4, characterized in that, In step (1), the thickness of the conductive seed layer is 0.05~0.5μm; In step (2), the thickness of the nickel-coated copper metal layer is 1~15μm.
6. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 4, characterized in that, In step (1), the conductive seed layer is a copper layer, a silver layer, or a nickel layer; In step (2), the electroplating process uses a plating solution containing copper salt and nickel salt. In the resulting nickel-coated copper metal layer, the mass percentage of nickel is 5-30% and the mass percentage of copper is 70-95%.
7. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 1, characterized in that, In step S1, the wave-transparent composite material is a glass fiber reinforced resin matrix composite material or a quartz fiber reinforced resin matrix composite material; The resin is epoxy resin or bismaleimide resin; In step S2, the laser engraving equipment is an ultraviolet laser engraving machine or a fiber laser engraving machine, and the line width accuracy of laser etching is controlled within ±0.05mm. In step S2, the preset periodic frequency selection surface pattern is at least one of dipole array, Jerusalem cross array, square ring array or complementary open resonant ring array.
8. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 1, characterized in that, In step S1, the co-curing molding process is autoclave molding, compression molding, or vacuum bag molding; The curing temperature range is 80~200℃, and the pressure range is 0.1~1.0MPa.
9. The method for preparing a curved frequency-selective surface based on conductive nonwoven fabric according to claim 1, characterized in that, In step S2, the depth of laser etching is controlled to be 1.5 to 5.0 times the thickness of the conductive nonwoven fabric, and not less than 50 μm.
10. A curved frequency selective surface based on conductive nonwoven fabric, characterized in that, A frequency-selective curved surface based on conductive nonwoven fabric obtained by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Airplane ground electromagnetic protective film based on flaky silver / graphite conductive paste
CN121394902A
Honeycomb conformal electromagnetic metasurface
CN121688416A
Composite super-structure surface unit with microwave window and infrared focusing and design method
CN121840203A